Essays in monetary economics - Johnson, Harry G. (London : Allen & Unwin, 1967)
This volume brings together essays and articles in the general field of monetary economics prepared for a variety of purposes over the past four years. It is made up of ten chapters with discussion centered on monetary theory, policies and fiscal problems.
Includes index
.
usc 29/06/2017
Loans
Keywords: Money; Monetary policy; Fiscal policy